THE SIGNIFICANCE OF MODIFIED PIRO SCORING WITH NLR BIOMARKER ON ENHANCING MORTALITY PREDICTION OF PATIENTS WITH VENTILATORSâASSOCIATED PNEUMONIA IN INTENSIVE CARE UNIT - Senapathi, Tjokorda Gde Agung; Budiarta, I Gede; Panji, Putu Agus Surya; Aprilnita, Aida (Bali Journal of Anesthesiology, 2018)
Ventilator-associated pneumonia (VAP) is a pulmonary infection that occurs as a mechanical ventilator-related disease which accounts for almost 80% of hospital-acquired pneumonia with of high mortality rate, lengthens the hospital-stay rate and increases health costs. To provide a description of the likelihood of the patients life expectancy, mortality, and prognosis of patients in ICU, a scoring system should be utilized in order to assess the severity of the disease and estimate mortality during hospital treatment. The PIRO scoring system is a comprehensive concept that provides good validity and derivation in predicting mortality risk in a wide range severity of the disease so that it is very useful in the selection or categorization of patients, especially those admitted to the ICU with VAP. A conjunction or integration with a simple biomarker such as Neutrophil-to-lymphocyte ratio (NLR) provides a better performance of the tool in regards to the predictive value in VAP mortality risk estimation. Since the NLR has a strong predictive value, is simple, low-cost, and easily available compared to other biomarkers, therefore it is practical and useful for prognostic indications for VAP with conjunction with the PIRO score where medical facilities are lacking.